2014
DOI: 10.3109/09513590.2014.929658
|View full text |Cite
|
Sign up to set email alerts
|

Desogestrel versus danazol as preoperative treatment for hysteroscopic surgery: a prospective, randomized evaluation

Abstract: The aim of this single-center, prospective, randomized, parallel-group study was to compare desogestrel and danazol as preoperative endometrial preparation for hysteroscopic surgery. We enrolled 200 consecutive eligible patients, in reproductive age, with endouterine diseases. Pre- and post-treatment characterization of endometrium was performed by hysteroscopic visual observation and histologic confirmation. The enrolled patients were randomly assigned to two groups: 100 were treated with 75 μg of desogestrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…To date, hysteroscopy represents a widely accepted method for the management of several gynecological conditions [ 16 20 ] or even to confirm ultrasound findings [ 21 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, hysteroscopy represents a widely accepted method for the management of several gynecological conditions [ 16 20 ] or even to confirm ultrasound findings [ 21 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lagana et al 112 reported on a comparative study of desogestrel and danazol as a preoperative endometrial preparation for hysteroscopic surgery. Their observations were that desogestrel caused less side effects and presented obvious outcomes in inducing endometrial atrophy, this allowed for a better intraoperative management and was shown to cause less side effects during treatment.…”
Section: Conservative Non-surgical Treatmentmentioning
confidence: 99%
“…They did two randomized controlled trials comparing cervical dilatation with laminaria (25.9 ± 5.8 mm) which was less than vaginal and greater than oral misoprostol but the difference was not significant 21,25 . The current study focused on cervical priming methods, however, recent literature described several hormonal methods such as desogestrel to optimize the outcome of this surgery in terms of endometrial visibility, operating time and the occurrence of complications 26–28 …”
Section: Discussionmentioning
confidence: 85%